The Elbow Principles of Surgical Treatment and Rehabilitation (Springer International Publishing, 2018)
This book provides readers with detailed guidance on the evaluation, diagnosis, and treatment of injuries and disorders of the elbow, including dislocation, complex instability, articular fractures, epicondylitis and epitrochleitis, distal biceps and triceps tendon injuries, peripheral nerve pathology, snapping triceps syndrome, elbow stiffness, and upper limb compartment syndrome. The choice between conservative and surgical treatment in different settings is clearly explained, and detailed advice offered on selection of surgical technique. A separate section provides a deeper understanding of the most common sports-related elbow pathologies, and their management, based on careful correlation with the movements performed by athletes in particular sports. Extensive consideration is also given to rehabilitation and physiotherapy protocols. This book will be of value for all orthopedic surgeons and other specialists who care for patients with elbow injuries, which can represent a challenge even to the more experienced.